1981
DOI: 10.1002/j.2161-1920.1981.tb01216.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Assessment of Job‐Related Skills

Abstract: An important aspect of finding and retaining employment is a person's level of occupational skills. Little information, however, is currently available on the comparative levels of job‐related skills among both unemployed and successfully‐employed adults. This study, using direct‐observation techniques, analyzes the occupational skills of these two groups. The results show that employed adults performed significantly better than unemployed adults on each of 13 job‐related skills assessed. These differences wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Further research is needed to determine if this type of training will be helpful to others who have difficulty maintaining jobs. Recent research has found the chronically unemployed to be deficient in vocational interpersonal skills (Mathews et al, 1981). Further research could also determine whether training for the chronically unemployed that focuses on the skills needed to maintain a job would be a useful addition to training that focuses on the skills needed to find a job (e.g., Azrin & Besalel, 1980).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research is needed to determine if this type of training will be helpful to others who have difficulty maintaining jobs. Recent research has found the chronically unemployed to be deficient in vocational interpersonal skills (Mathews et al, 1981). Further research could also determine whether training for the chronically unemployed that focuses on the skills needed to maintain a job would be a useful addition to training that focuses on the skills needed to find a job (e.g., Azrin & Besalel, 1980).…”
Section: Resultsmentioning
confidence: 99%
“…These critical behaviors are primarily social skills, with 10 of the 13 involving social interactions. Subsequent research has indicated that unemployed persons are deficient in these skills (Mathews, Whang, & Fawcett, 1981).…”
mentioning
confidence: 99%
“…In addition, Calabrese and Hawkins (1988) devised a measure to assess social behaviour at work while conducting job-related social skills training with female prisoners. Mathews, Whang, and Fawcett (1981) also described an occupational skills assessment instrument for measuring job-related skills of normal adults. However, among the instruments, none is designed in a way that has considered the special needs and problems of people who have schizophrenia.…”
Section: Assessing Work Skillsmentioning
confidence: 99%
“…A need for social skills training programs that include social skills essential for successful employment currently exists. Mathews, Whang, and Fawcett (1981) identified 13 jobrelated social skills, including accepting suggestions from an employer, providing constructive criticism, and explaining a problem to a supervisor; more efforts in this direction are needed. It is hoped that special educators who serve older mildly handicapped students will use the evaluation checklist included in this article to identify a social skills training program that can be integrated into the existing secondary curriculum.…”
mentioning
confidence: 97%